New Brazilian species of Folsomides Stach (Collembola: Isotomidae) - de Mendonça, Maria Cleide; Da Rocha Neves, Ana Carolina (Zootaxa, 2020)
A new blind species, Folsomides cariocus sp. nov., which belongs to the F. parvulus group sensu Fjellberg (1993), is described and illustrated based on material collected in compacted clay soil covered by undergrowth and no litter around the bee nest holes at the Botanical Garden, located in Rio de Janeiro City. The new species is very similar to F. parvulus Stach, 1922 but differs mainly due to the absence of eyes. Synonymies based on ocular variations and pigmented spots were discussed and a table for the group parvulus species is present.